Adjusting to the Receiving Country Outside the Sport Environment: A Composite Vignette of Canadian Immigrant Amateur Elite Athlete Acculturation. Issue 3 (3rd July 2017) - Schinke, Robert J.; Blodgett, Amy T.; McGannon, Kerry R.; Ge, Yang; Oghene, Odirin; Seanor, Michelle
Abstract : This qualitative project is focused on the challenges that newcomer athletes revealed when they considered their earliest encounters with a receiving culture during general daily life. Conversational interviews with 24 national and international amateur newcomer athletes were subjected to interpretive thematic analysis and developed into a composite vignette. This vignette unearths three themes revealing hope (theme: opportunities abound); uncertainty and fear (theme: weighing the risks for the journey ahead); and anger, humiliation, and hardening (theme: public stonings). Understanding the fluidities within the vignette will permit practitioners to explore the uncertainties of acculturation and find entry points to support athlete acculturation.